Long-term sedation with remimazolam besylate versus propofol in critically ill patients during invasive mechanical ventilation: a study protocol for a multicenter randomized non-inferior trial - Xiaobo Yang; Yun Tang; Ruofei Du; Yuan Yu; Jiqian Xu; Jiancheng Zhang; Hong Liu; Xiaojing Zou; Lehao Ren; Shiying Yuan; You Shang (Frontiers Media S.A., 2023)
Background: Remimazolam besylate is a novel ultra-short-acting benzodiazepine that can potentially be a safe and effective sedative in intensive care units. This study aims to assess whether remimazolam besylate is not inferior to propofol in maintaining mild-to-moderate sedation in critically ill patients receiving long-term mechanical ventilation.Methods and analysis: This is a multicenter, randomized, single-blind, propofol-controlled, non-inferiority study. Eligible patients are randomly assigned to receive remimazolam besylate or propofol in a 1:1 ratio to maintain a Richmond Agitation-Sedation Scale score between −3 and 0. When patients are under-sedated, rescue sedation of dexmedetomidine is added. The primary outcome is the percentage of time in the target sedation range. The secondary outcomes are hours free from the invasive ventilator in 7 days, successful extubation in 7 days, and weaning time, the length of intensive care unit stay, the length of hospital stay, and mortality in 28 days. Modified intention-to-treat and safety analysis is performed.Clinical trial registration number:https://clinicaltrials.gov/ct2/show/NCT05555667.